Designing in vitro Blood-Brain Barrier Models Reproducing Alterations in Brain Aging - Osipova, Elena D.; Komleva, Yulia K.; Morgun, Andrey V.; Lopatina, Olga L.; Panina, Yulia A.; Olovyannikova, Raissa Ya.; Vais, Elizaveta F.; Salmin, Vladimir V.; Salmina, Alla B. (Frontiers in Aging Neuroscience, 2018)
Blood-brain barrier (BBB) modeling in vitro is a huge area of research covering study of intercellular communications and development of BBB, establishment of specific properties that provide controlled permeability of the barrier. Current approaches in designing new BBB models include development of new (bio)scaffolds supporting barriergenesis/angiogenesis and BBB integrity; use of methods enabling modulation of BBB permeability; application of modern analytical techniques for screening the transfer of metabolites, biomacromolecules, selected drug candidates and drug delivery systems; establishment of 3D models; application of microfluidic technologies; reconstruction of microphysiological systems with the barrier constituents. Acceptance of idea that BBB in vitro models should resemble real functional activity of the barrier in different periods of ontogenesis and in different (patho)physiological conditions leads to proposal that establishment of BBB in vitro model with alterations specific for aging brain is one of current challenges in neurosciences and bioengineering. Vascular dysfunction in the aging brain often associates with leaky BBB, alterations in perivascular microenvironment, neuroinflammation, perturbed neuronal and astroglial activity within the neurovascular unit, impairments in neurogenic niches where microvascular scaffold plays a key regulatory role. The review is focused on aging-related alterations in BBB and current approaches to development of “aging” BBB models in vitro.